Effects of pre-course preparation using a serious smartphone game on advanced life support knowledge and skills -A randomized controlled trial. (25th November 2020) - Kotruchin, P; Phungoen, P; Mitsungnern, T
Abstract: Background: Over the past several years, gamified learning has been growing in popularity in various medical educational contexts including cardiopulmonary resuscitation (CPR) training. Furthermore, prior work in Basic Life Support (BLS) training has demonstrated the benefits of serious games as a method for pre-training among medical students. However, there is little evidence to support these benefits with regard to Advanced Life Support (ALS) training Objective: We compare the effects of a brief pre-course ALS preparation course using a serious smartphone game on students' knowledge, skills, and perceptions in this area with those of conventional ALS training alone. Methods: A serious game (Resus Days) was developed by a Thai physician based on global ALS clinical practice guidelines. Fifth-year medical students were enrolled and randomized to either a game group or a control group. Participants in both groups attended a traditional ALS lecture, but the game group was assigned to play Resus Days for 1 hour before attending the lecture and as wished after that. All students underwent conventional ALS training, and their abilities were evaluated using multiple choice questions and with hands-on practice on a mannequin. Subjects' attitudes and perceptions about the game were evaluated using a questionnaire. Results: A total of 105 students participated in the study and were randomly assigned to either the game group (n=52) or the control group (n=53). Students in the game group performed better on the ALS algorithm knowledge posttest than those in the control group (17.22±1.93 vs 16.60±1.97, P=0.01; adjusted mean difference [AMD] 0.93, 95% CI 0.21–1.66;). The game group's pass rate on the skill test was also higher, but not to a statistically significant extent (79% vs 66%, P=0.09; adjusted odds ratio [AOR] 2.22, 95% CI 0.89–5.51). Students also indicated high satisfaction with the game (9.02±1.11 out of 10). Conclusions: Engaging in game-based preparation prior to an ALS training course resulted in greater medical students' algorithm knowledge scores than attending the course alone. Funding Acknowledgement: Type of funding source: None